PENGEMBANGAN BUDAYA SEKOLAH SEBAGAI PENGUATAN PENDIDIKAN KARAKTER RELIGIUS SISWA SEKOLAH DASAR NEGERI 3 SUKAWATI - I Nyoman Sueca (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The development of values in character education through school culture includes all activities carried out by school principals, teacher counselors, and administrative staff when communicating with students and using school facilities. School culture is the atmosphere of school life where members of the school community interact with each other. The implementation of character education in the learning process in the classroom cannot be separated from various other activities outside the classroom or even outside school. In the classroom, the teacher can start with an introduction to the values that will be developed during the learning process, then the teacher guides students to be actively involved throughout the learning process. Strengthening religious character education in the learning process in the classroom cannot be separated from various activities both outside the classroom or even outside school. Character education has a higher meaning than formal education, because character education is not only related to the problem of right and wrong, but how to instill habits (habits) about good things in life, so that students have high awareness and understanding, and concern and commitment to apply virtue in daily life. The development of school culture carried out by teachers at SD Negeri 3 Sukawati is all efforts made by school residents who have been directed by the principal to create an atmosphere and learning conditions in the classroom to be conducive and fun and can motivate students to study well in accordance with his abilities. Strengthening the religious character of students built by school residents needs to be created through the establishment of a conducive learning atmosphere in the school environment, including the classroom environment. Explicitly the factors that influence the success of the learning process in the classroom in developing school culture as a strengthening of the religious character education of students at SD Negeri 3 Sukawati include teacher competence, learning methods used, curriculum, facilities and infrastructure, and a good learning environment. natural environment, psychology and culture.